Influence of chronic stress in pregnant women on development of eating habits in their offspring in postnatal life - Szydełko, Joanna; Szydełko, Magdalena; Piątek, Daniel; Tuzim, Kamila; Boguszewska-Czubara, Anna (European Journal of Clinical and Experimental Medicine, 2016)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Nowadays, stress became an integral part of human life and accompanies it from conception to death. Effects of its influence on human organism are mainly dependent on patterns of reaction programmed already in prenatal period. Negative stimuli lead to activation of hypothalamic– pituitary–adrenal axis and autonomic nervous system. Chronic tension results in significant increase in the level of stress hormones which break natural and enzymatic placental barrier and permeate to fetus’ bloodstream thus contributing to significant disorders in development of eating habits. A consequence of this situation is considerable risk of overweight in postnatal life of children of those mothers who were subjected to chronic stress during pregnancy. Exposition of pregnant woman to stress stimuli also has significant implications on developing central nervous system. Disorders in brain transmission pathways, especially of hypothalamus as an organ which has a major role in central regulation of food intake, may significantly influence amount and calorific value of chosen foods. Attempt to explain complex mechanisms between chronic stress in prenatal period and excessive weight in postnatal period is paramount because of rapidly increasing percentage of people with such affliction, mainly among children and teenagers, and multitude of complications involving all systems of human organism.